The use of a genetic algorithm to determine the optimal operating conditions for a low-temperature ORC system - Grzebielec, Andrzej; Szelągowski, Adam; Łapka, Piotr; Cieślikiewicz, Łukasz; Seredyński, Mirosław (International Conference “Environmental Engineering”, 2023)
Organic Rankine Cycle (ORC) devices are systems that implement the basic Rankine cycle, but use an organic medium instead of water. These devices can use low-temperature heat, but it should be remembered that the achievable efficiency decreases as the source temperature decreases. Previous publications have shown that maximizing capacity, rather than efficiency, is the main goal of the ORC system. This can be achieved by establishing the correct operating conditions, while ensuring the correct mass flow of the working medium to each component. For instance, the expander must reach the required rotational speed. This work focuses on using genetic algorithms to determine optimal operating conditions and maximize capacity. A genetic algorithm was developed for a newly built ORC device, enabling determination of optimal operating conditions. The results were implemented in the device driver and validated experimentally, confirming that genetic algorithms can easily achieve the desired effect.